If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-3v + -4) = 38 Reorder the terms: 2(-4 + -3v) = 38 (-4 * 2 + -3v * 2) = 38 (-8 + -6v) = 38 Solving -8 + -6v = 38 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -6v = 38 + 8 Combine like terms: -8 + 8 = 0 0 + -6v = 38 + 8 -6v = 38 + 8 Combine like terms: 38 + 8 = 46 -6v = 46 Divide each side by '-6'. v = -7.666666667 Simplifying v = -7.666666667
| 17x^2-138x-290= | | 7(b+9)=112 | | 3x^3-2x^2-x=70 | | 33+6x=3x | | 13.5b-6.5=-2.3b+8.3 | | 13.5b-6.5=-2.3+8.3 | | 2x+3y=59 | | 36=4x-12 | | -5+2k=5 | | 7x=7+x | | 12x^3-8x^2-4x-35=0 | | 11t(4-t)=2(5-3t) | | sqrt(x+2*sqrt(x-1))-sqrt(x-2*sqrt(x-1))=2 | | 6x+7=100+3x-20 | | 6x+7=1003x-20 | | 36x^2-476x-2462=0 | | x^2+5x-10=14 | | -8x-34=9x | | 2y-36=5y-2y | | 2(26+-2y+-3z)+3y+z=34 | | 3(26-2y-3z)+3y+z=34 | | 3(26-2y-3z)+2y+z=39 | | X-2y+9z=6 | | -9x+11=2x | | 15X^4-(30X^2)+7=0 | | 4m+5=27 | | 4(c+10)-146=6 | | x=26+-2y+-3z | | 11x-11=4x+9 | | 3(4-3x)=9(5-2x) | | 2w+2.9=13.5 | | 5x+12-(2x-12)=-3x+9 |